Metformin, Rapamycin, or Nicotinamide Mononucleotide Pretreatment Attenuate Cognitive Impairment After Cerebral Hypoperfusion by Inhibiting Microglial Phagocytosis - Yu, Mengdi; Zheng, Xiaoying; Cheng, Fangyu; Shao, Bei; Zhuge, Qichuan; Jin, Kunlin (Frontiers in Neurology, 2022)
Vascular cognitive impairment (VCI) is the second leading form of dementia after Alzheimer’s disease (AD) plaguing the elder population. Despite the enormous prevalence of VCI, the biological basis of this disease has been much less well studied than that of AD, with no specific therapy currently existing to prevent or treat VCI. As VCI mainly occurs in the elderly, the role of anti-aging drugs including metformin, rapamycin, and nicotinamide mononucleotide (NMN), and the underlying mechanism remain uncertain. Here, we examined the role of metformin, rapamycin, and NMN in cognitive function, white matter integrity, microglial response, and phagocytosis in a rat model of VCI using bilateral common carotid artery occlusion (BCCAO). BCCAO-induced chronic cerebral hypoperfusion could cause spatial working memory deficits and white matter lesions (WMLs), along with increasing microglial activation and phagocytosis compared to sham-operated rats. After pretreatment of metformin, rapamycin, or NMN for 14 days following BCCAO, we found the cognitive impairment was significantly improved in BCCAO rats pretreated with anti-aging drugs compared with the vehicle group by analysis of Morris water maze test and new object recognition test. Pretreatment of metformin, rapamycin, or NMN also ameliorated BCCAO-induced WMLs compared with the vehicle group, as evidenced by a decrease of myelin basic protein (MBP, a marker for myelin) levels and a concurrent increase in SMI32 (a marker for demyelinated axons) intensity and SMI32/MBP ratio, which was further confirmed by Luxol fast blue (LFB) staining. We further found that pretreatment of metformin, rapamycin, or NMN reduced microglial activation and the number of M1 microglia (Iba1+/CD68+) and increased the number of M2 microglia (Iba1+/CD206+) compared to the vehicle group. Importantly, the number of MBP+/Iba1+/CD206+ microglia was also significantly reduced in the BCCAO rats pretreated with metformin, rapamycin, or NMN compared with the vehicle group, suggesting that anti-aging drugs suppress microglial phagocytosis after BCCAO. No significant difference was found between the groups treated with metformin, rapamycin, or NMN. Our data suggest that metformin, rapamycin, or NMN could protect or attenuate cognitive impairment and WMLs through modifying microglial polarization and inhibiting phagocytosis, which may open a new avenue for VCI treatment.